Pengaruh Profitabilitas, Ukuran Perusahaan, Cash Holding, dan Leverage terhadap Nilai Perusahaan pada Perusahaan Sektor Perindustrian di Bursa Efek Indonesia - Wennie Valencia (LPPM Universitas Widya Dharma Pontianak, 2025)
This study aims to analyze the effect of profitability, company size, cash holding, and leverage on company value in 42 companies. The form of research used in this study is causal associative research obtained by sampling using a purposive sampling method with the criteria (1) companies that conducted an IPO before 2019, (2) companies that published financial reports ending on December 31. The secondary data source used is the financial report on the Indonesia Stock Exchange. The statistical analysis approach was carried out using SPSS 26 with descriptive test data analysis methods, classical assumptions, multiple linear regression analysis, F test and t test. The results of the study indicate that profitability and cash holding have a positive effect on company value, company size and leverage have a negative effect on company value.